Low-temperature high-efficiency low-carbon alkane catalytic oxidation catalyst and preparation method thereof

By designing the non-stoichiometric NixCo3-xO4 spinel nanocluster with the composite active sites of precious metals and transition metals in low-carbon alkane catalysts, the problem of low-conversion efficiency of existing catalysts is solved, and the low-temperature and efficient catalytic oxidation effect is achieved.

CN119746887AActive Publication Date: 2025-04-04SINOCAT ENVIRONMENTAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411941564.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

When existing low-carbon alkane catalysts treat low-concentration low-carbon alkanes, the catalyst has a high ignition temperature and low conversion efficiency, making it difficult to effectively catalyze oxidation at low temperatures.

Method used

By designing the non-stoichiometric NixCo3-xO4 spinel nanoclusters with the composite active sites of noble metals and transition metals, and in combination with catalytic materials, a low-temperature and high-efficiency catalytic oxidation low-carbon alkane catalyst was prepared.

Benefits of technology

It realizes low-temperature and efficient catalytic oxidation of low-carbon alkanes, reduces the ignition temperature of T50 and T99, and improves the low-temperature adsorption capacity and stability of the catalyst, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746887A_ABST
    Figure CN119746887A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly discloses a low-temperature efficient low-carbon alkane catalytic oxidation catalyst and a preparation method thereof.The catalyst comprises a catalytic material, an active component and NixCo3-xO4 spinel nanoclusters, the active component and the NixCo3-xO4 spinel nanoclusters are loaded on the catalytic material, x is 0.4-0.99, the active component is a composite metal oxide composed of precious metal and transition metal, and the NixCo3-xO4 spinel nanoclusters are loaded on the catalytic material. According to the catalyst, an active component is firstly combined with a catalytic material, and then is combined with a non-stoichiometric ratio Ni < x > Co < 3-x > O < 4 > spinel nanocluster; in the catalyst, the content of the Ni < x > Co < 3-x > O < 4 > spinel nanocluster accounts for 1.0 to 20.0 weight percent; the content of the noble metal accounts for 0.1-2.0 wt%, and the content of the transition metal accounts for 1.0-20.0 wt%. The catalyst disclosed by the invention has good low-temperature catalytic purification performance and good stability on low-carbon alkane, can be widely applied to industrial waste gas purification industries such as petroleum, chemical engineering and refining, realizes low-temperature efficient catalytic combustion purification on various toxic and harmful waste gases such as low-carbon alkane, and is simple in preparation process and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes and a preparation method thereof. Background Art

[0002] Volatile organic compounds (VOCs) are toxic and harmful pollutants. x , PM 2.5 The formation of ozone or haze seriously threatens human health. VOCs include alkanes, olefins, aromatic hydrocarbons, aldehydes, ketones and other major categories. Under the increasingly stringent emission standards and the strong promotion of national and local policies, the emission control of VOCs from industrial sources has received widespread attention, especially in industrial fields such as petroleum, petrochemicals and chemicals. VOCs pollution control can be divided into adsorption, incineration, catalytic oxidation, biological methods and membrane separation methods. Among them, catalytic oxidation technology is one of the most promising technologies for removing VOCs because of its low energy consumption and no secondary pollution; and the development of high-performance catalytic oxidation catalysts is the key to achieving waste gas purification and green production.

[0003] VOCs catalytic oxidation catalysts usually use precious metals such as platinum and palladium as active components. These precious metals can activate hydrocarbons and oxygen at low temperatures, so that the two can activate CH or enhance the adsorption of low-carbon molecules through mechanisms such as LH or MvK, and catalytic reactions occur at the active sites of the catalyst, showing excellent low-temperature catalytic oxidation activity. However, low-carbon alkanes, such as methane, ethane, propane or isobutane, have strong carbon-hydrogen bonds that are difficult to break. When processing low-concentration low-carbon alkanes, the existing low-carbon alkane catalysts have high catalyst ignition temperatures and low conversion efficiencies. In actual industrial applications, the T of general low-carbon alkane catalysts is generally 50 Greater than 340℃, T 99 When the temperature reaches above 450°C, the high price of precious metals determines that the precious metal loading in the oxidation catalyst is limited, and the performance of the catalyst is difficult to further improve.

[0004] In order to improve the low temperature performance of low carbon alkane catalyst, patent CN117563629A discloses a monolithic catalytic material for low carbon alkane oxidation and its preparation method and application, wherein the palladium source is dissolved in hydrochloric acid, and then the transition metal nitrate of the VIII main group is added, after stirring and clarifying, a cerium oxide carrier is added, the pH is adjusted to 9-9.5, stirred and allowed to stand, and calcined to obtain a catalyst powder; the catalyst powder is loaded on the surface of the metal aluminum fiber carrier by a wet impregnation method to obtain a monolithic catalytic material, and the mass percentage of palladium in the monolithic catalyst is 0.5-1.0%. The material has abundant oxygen vacancies and a high palladium dispersion. Compared with the unmodified pure palladium-loaded catalyst, the monolithic catalyst modified with palladium by a strong electron-donating transition metal has better low carbon alkane oxidation performance, and exhibits excellent water resistance, CO resistance and stability, and has reproducibility. Although the above method can provide oxygen vacancies by adding transition metals to precious metals, the oxygen vacancies provided are limited and cannot effectively improve the low temperature performance of low carbon alkane catalysts.

[0005] Therefore, providing a low-carbon alkane catalyst that can fully exert its catalytic performance at low temperatures is an urgent problem to be solved in the art. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of high catalyst ignition temperature and low catalyst conversion efficiency when the existing low-carbon alkane catalyst is used to purify low-carbon alkanes, and to provide a low-temperature and high-efficiency catalytic oxidation catalyst for low-carbon alkanes and a preparation method thereof, which have outstanding low-temperature and high-efficiency performance when purifying low-concentration low-carbon alkanes.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A low-temperature and high-efficiency catalyst for catalytic oxidation of light alkanes, the catalyst comprising a catalytic material and an active component supported on the catalytic material, Ni x Co 3-x O4 spinel nanoclusters, x is 0.4 to 0.99, the active component is a composite metal oxide composed of a noble metal and a transition metal, the catalyst is prepared by first combining the active component with the catalytic material, and then combining with the Ni x Co 3-x O4 spinel nanoclusters are combined; in the catalyst, the Ni x Co 3-x The content of O4 spinel nanoclusters accounts for 1.0-20.0wt%; the content of the noble metal accounts for 0.1-2.0wt%; and the content of the transition metal accounts for 1.0-20.0wt%.

[0009] In the above technical solution, the catalyst is a mixture of active components of precious metal (PGM), transition metal (TM) and catalytic material (MO y ) and then combined with non-stoichiometric Ni x Co 3-x O4 spinel nanoclusters are combined to finally prepare the desired catalyst Ni x Co 3-x O4-PGM-TM / MO y , referred to as N x C 3-x -PT / M, wherein the composite metal oxide composed of the noble metal and the transition metal is a bimetallic oxide or a trimetallic oxide, N x C 3-x -In PT / M catalyst, non-stoichiometric Ni x Co 3-x The content of O4 spinel accounts for 1.0wt% to 20.0wt%, the content of precious metal accounts for 0.1wt% to 2.0wt%, and the content of transition metal accounts for 1.0wt% to 20.0wt%.

[0010] The catalyst of the present invention is designed by non-stoichiometric ratio of Ni x Co 3-x O4 spinel nanoclusters, noble metal and transition metal composite active sites, spinel nanoclusters, noble metals, transition metals and catalytic materials work together, because Ni x Co 3-x O4 spinel nanoclusters have good redox properties. They are prepared in catalysts to have more defect sites, which makes the precious metals more dispersed on the catalytic materials. At the same time, transition metals make the active sites of precious metals behave more as metal valence active sites, enhance the stability and redox properties of active species, and enrich the active oxygen species on the catalyst surface, thereby further synergistically improving the low-temperature adsorption capacity of light alkanes, achieving low-temperature and efficient catalytic oxidation of light alkanes, and laying the foundation for long-term satisfaction of 99% good ignition performance.

[0011] As a preferred embodiment of the present invention, the noble metal is at least one of Pt and Pd.

[0012] As a more preferred embodiment of the present invention, the content of the precious metal is 0.5-1 wt%.

[0013] As a more preferred embodiment of the present invention, the non-stoichiometric Ni x Co 3-x The content of O4 spinel nanoclusters is 5-15wt%.

[0014] As a preferred embodiment of the present invention, the transition metal is at least one of tungsten (W), cobalt (Co), molybdenum (Mo), niobium (Nb), nickel (Ni), zirconium (Zr), titanium (Ti), vanadium (V), and manganese (Mn).

[0015] As a more preferred embodiment of the present invention, the transition metal content accounts for 3.0 to 15.0 wt %. More preferably, the transition metal content accounts for 10 to 15.0 wt %.

[0016] As a preferred embodiment of the present invention, the catalytic material is at least one of aluminum oxide, silicon oxide, titanium oxide, cerium oxide and zirconium oxide.

[0017] Another aspect of the present invention provides a method for preparing a catalyst for low-temperature and high-efficiency catalytic oxidation of light alkanes, comprising the following steps:

[0018] S1. Prepare a mixed solution of soluble precursor salts of precious metals and transition metals, add a first auxiliary agent to form solution A, stir solution A at a temperature of 40 to 90° C. for 1 h to 4 h, then add a catalytic material to solution A, the mass ratio of the catalytic material added to solution A is 0.8 to 1.2, and continue stirring at a temperature of 40 to 90° C. for 3 h to 10 h. After completion, dry and calcine to obtain a PT / M catalyst;

[0019] A sodium hydroxide-ammonia aqueous solution with a pH of 8.5 to 11 is prepared to obtain a solution C, the PT / M catalyst is added to the solution C, and a suspension containing the PT / M catalyst is obtained after stirring, and the suspension is kept at a temperature of 40 to 90° C. for 1 h to 6 h;

[0020] A mixed solution of a nickel soluble precursor salt and a cobalt soluble precursor salt is prepared to obtain a solution B, wherein the molar ratio of Ni to Co is x:(3-x), and x is 0.4 to 0.99;

[0021] S2. Add the solution B dropwise into the suspension under stirring, with a stirring rate of 100 to 300 r / min and a dropping duration of 1 h to 3 h; then age, filter, wash, dry and calcine in sequence to obtain a catalyst for catalytic oxidation of light alkanes.

[0022] In the above technical solution, the active components of precious metal (PGM), transition metal (TM) and catalytic material (MO y ) to prepare a PT / M catalyst; then the PT / M catalyst is suspended in a sodium hydroxide-ammonia solution, and the pH of the solution is controlled to be 8.5-11 to create an alkaline environment for the subsequent Ni x Co 3-xThe method provides conditions for the formation and combination of O4 spinel nanoclusters; then, a mixed solution of nickel and cobalt is prepared according to the designed non-stoichiometric ratio, and solution B is added to the suspension by a dropwise addition method. The size of the formed spinel nanoclusters is controlled by controlling the feed ratio, temperature and concentration, and in-situ synthetic crystallization is used to fully combine them, and finally a catalyst for catalytic oxidation of light alkanes is obtained.

[0023] As a preferred embodiment of the present invention, the soluble precursor salt of the noble metal is at least one of nitrate, acetate and oxalate, and the soluble precursor salt of the transition metal is at least one of nitrate, acetate and oxalate.

[0024] As a preferred embodiment of the present invention, the first auxiliary agent is at least one of citric acid, oxalic acid, etc., and the first auxiliary agent content and the precious metal content are added in a molar ratio of 1.5 to 5:1; more preferably, the first auxiliary agent content and the precious metal content are added in a molar ratio of 3:1.

[0025] As a preferred embodiment of the present invention, the aging process is carried out at room temperature for 10 to 24 hours.

[0026] As a preferred embodiment of the present invention, the washing process uses deionized water for 1 to 3 times.

[0027] As a preferred embodiment of the present invention, the drying process is carried out at 90 to 120° C. for 5 to 10 hours.

[0028] As a preferred embodiment of the present invention, the calcination adopts a continuous calcination process and is divided into two calcinations. The first calcination condition is calcination at 300-450°C for 3-5h; the second calcination condition is calcination at 650-900°C for 3-7h.

[0029] The present invention also provides an integral catalyst, which comprises a carrier and a catalytic coating, wherein the catalytic coating comprises the above-mentioned low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes.

[0030] As a preferred embodiment of the present invention, the carrier comprises a porous metal honeycomb carrier or a porous ceramic honeycomb carrier, and a catalyst coating of a certain thickness is coated on the carrier through single or multiple coatings.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The catalyst of the present invention is designed with a non-stoichiometric ratio of Ni x Co 3-x O4 spinel nanoclusters, noble metal and transition metal composite active sites, synergize with catalytic materials, because Ni x Co 3-xO4 spinel nanoclusters have good redox properties. They are prepared in catalysts to have more defect sites, and precious metals have better dispersion on catalytic materials. At the same time, transition metals make the active sites of precious metals behave more as metal valence active sites, enhance the stability and redox properties of active species, and enrich the active oxygen species on the catalyst surface, thereby further synergistically improving the low-temperature adsorption capacity of light alkanes and realizing low-temperature and efficient catalytic oxidation of light alkanes.

[0033] 2. The catalyst prepared by the present invention has good low-temperature ignition performance for low-concentration low-carbon alkanes. -1 Catalytic oxidation of propane, T 50 The temperature range is 290~315℃, T 99 The temperature range is 350-365°C. The stability test is carried out at 350°C. The catalytic efficiency of the catalyst prepared by the present invention can reach more than 93%. The test time is 200h and the good stability is maintained. The fluctuation range of the catalytic efficiency is less than 1.0%, and it still has good stability at a high conversion rate.

[0034] 3. The catalyst provided by the present invention has good low-temperature ignition performance for low-carbon alkanes such as methane, ethane and propane, and is suitable for petroleum refining and chemical plant scenarios such as acrylic acid, acrylonitrile, phenol acetone, etc., and can achieve low-temperature and high-efficiency catalytic purification of low-carbon alkanes in exhaust gas. It has a large processing capacity, a wide range of applications, a simple process, and is easy to scale up for industrialization. The catalyst has high catalyst activity and good use effect, and has good industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of the preparation method of the catalyst for low-temperature and high-efficiency catalytic oxidation of light alkanes. DETAILED DESCRIPTION

[0036] In order to more clearly describe the invention purpose, technical scheme and technical effect advantages in the specific implementation case of the present invention, the scheme in the specific embodiment will be described in detail in combination with the drawings of the specification of the present invention. The specific technical scheme involved in the following specific embodiments is only for a clear and complete description of the innovative technical scheme of the present invention. It is only a part of the specific implementation scheme that can be adopted by the present invention, not all embodiments, and should not be understood as a limitation on the innovative scheme of the present invention. Any scheme adopting the same inventive concept of the present invention should be included in the protection scope of the present invention.

[0037] Secondly, the description of the drawings in the specific embodiments of the present invention is only for the convenience of technical personnel to understand the solution of the present invention. The partial details in the drawings are for the convenience of clearly presenting the technical solution. It should not be considered that all technical features in the drawings must be included in the specific implementation cases, and the detailed features in the drawings should not be identified as additional limitations on the innovative technical solution of the present invention. The components in the various embodiments described and shown in the drawings can be combined and arranged according to different configurations, and these changes in combination and arrangement should be identified as part of the entire embodiment of the innovative solution of the present invention and included in the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment provides a low-temperature and high-efficiency catalyst for catalytic oxidation of light alkanes, wherein the active components are bimetallic oxides or trimetallic oxides composed of noble metals and transition metals, Ni x Co 3-x In O4 spinel nanoclusters, x is 0.5, N 0.5 C 2.5 Non-stoichiometric Ni in 4Pt1PdW / Al2O3 Catalyst 0.5 Co 2.5 The content of O4 spinel accounts for 5.0wt%, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, the content of transition metal WO3 accounts for 5.0wt%, and the catalyst is prepared by the following method:

[0040] 1) According to the content design, noble metal platinum nitrate, platinum nitrate and ammonium metatungstate are prepared into a mixed solution, and oxalic acid is added to form solution A, and the oxalic acid content and the noble metal content are added according to the molar ratio of 3:1;

[0041] 2) Place solution A in a water bath and stir continuously at a water bath temperature of 60°C for 2 hours. Add catalytic material alumina to solution A at a mass ratio of 0.9 to solution A; continue stirring at a water bath temperature of 60°C for 5 hours; then go through a muffle furnace drying and calcination process, drying process: 110°C @ 4 hours, calcination process: temperature: 400°C, time: 3 hours; obtain 4Pt1PdW / Al2O3 catalyst.

[0042] 3) Prepare a sodium hydroxide-ammonia aqueous solution with a pH control range of 10.5 to obtain solution C, then add the 4Pt1PdW / Al2O3 catalyst obtained in 2) to solution C, stir continuously to obtain a suspension containing the 4Pt1PdW / Al2O3 catalyst, and place in a water bath at 90°C for 3 hours.

[0043] 4) With the molar ratio of Ni to Co being 0.5:2.5, according to Ni 0.5 Co2.5 O4 accounts for 5wt% of the total mass of the catalyst, and the corresponding precursor salts of nickel nitrate and cobalt nitrate are mixed to obtain solution B; the molar concentration of 4Pt1PdW / Al2O3 catalyst in the suspension is required to be at least 2 times that of solution B, and the excess can ensure as much deposition as possible during the subsequent dropwise addition process,

[0044] 5) adding solution B to the suspension, stirring while adding dropwise, with a stirring rate of 200 r / min; time: 1 h; then aging, filtering, washing, drying, roasting and other processes are carried out in sequence to obtain N of Example 1 0.5 C 2.5 -4Pt1PdW / Al2O3 catalyst; wherein the aging process is at room temperature for 15 hours; the washing is performed three times with deionized water; the drying process is at 110°C@5 hours; a continuous roasting process is adopted, the first roasting temperature is 400°C, the time is 3 hours; the second roasting temperature is 750°C, the time is 5 hours.

[0045] Example 2

[0046] This example is similar to Example 1, except that the transition metal in this example is niobium, and the molar ratio of Ni to Co is 0.7:2.3. 0.7 C 2.3 -4Pt1PdNb / Al2O3, non-stoichiometric Ni in the catalyst 0.7 Co 2.3 The content of O4 spinel accounts for 5.0wt%, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, the content of transition metal NbO3 accounts for 5.0wt%, and the preparation method is the same as that in Example 1 to prepare the catalyst of this example.

[0047] Example 3

[0048] This embodiment is similar to embodiment 2, except that the transition metal in this embodiment is zirconium, Ni 0.7 Co 2.3 O4 accounts for 10wt% of the total mass of the catalyst. 0.7 C 2.3 -4Pt1PdZr / Al2O3, non-stoichiometric Ni in the catalyst 0.7 Co 2.3 The content of O4 spinel accounts for 10wt%, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, the content of transition metal ZrO2 accounts for 5.0wt%, and the preparation method is the same as that in Example 1 to prepare the catalyst of this example.

[0049] Example 4

[0050] This embodiment is similar to embodiment 3, except that the transition metal in this embodiment is molybdenum. 0.7 C 2.3 -4Pt1PdMo / Al2O3, non-stoichiometric Ni in the catalyst 0.7 Co 2.3 The content of O4 spinel accounts for 10wt%, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, the content of transition metal MoO3 accounts for 5.0wt%, and the preparation method is the same as that in Example 1 to prepare the catalyst of this example.

[0051] Example 5

[0052] This embodiment is similar to embodiment 1, except that in this embodiment, the precious metal is platinum, the transition metal is cobalt, the molar ratio of Ni to Co is 0.9:2.1, and N 0.9 C 2.1 -In PtCo / Al2O3 catalyst, non-stoichiometric Ni 0.9 Co 2.1 The content of O4 spinel accounts for 15.0wt%, the content of precious metal platinum accounts for 1.0wt%, and the content of Co3O4 accounts for 5.0wt%. The preparation steps are as follows:

[0053] 1) According to the content design, noble metal platinum nitrate and cobalt nitrate are prepared into a mixed solution, and citric acid is added to form solution A, and the citric acid content and the noble metal content are added according to the molar ratio of 3:1;

[0054] 2) Place solution A in a water bath and stir continuously at a water bath temperature of 60°C for 2 hours. Add catalytic material alumina to solution A at a mass ratio of 0.9 to solution A; continue stirring at a water bath temperature of 60°C for 5 hours; then go through a muffle furnace drying and calcination process, drying process: 110°C @ 4 hours, calcination process: temperature: 400°C, time: 3 hours; obtain PtCo / Al2O3 catalyst.

[0055] 3) Prepare a sodium hydroxide-ammonia aqueous solution with a pH control range of 10.5 to obtain solution C, then add the PtCo / Al2O3 catalyst obtained in 2) to the prepared sodium hydroxide-ammonia aqueous solution C, stir continuously to obtain a suspension C containing the PtCo / Al2O3 catalyst, and place in a water bath at a temperature of 90° C. for 3 h.

[0056] 4) With the molar ratio of Ni to Co being 0.9:2.1, according to Ni 0.9 Co 2.1 O4 accounts for 15.0wt% of the total mass and is added, and the corresponding precursor salts are nickel nitrate and cobalt nitrate; and they are mixed to obtain solution B;

[0057] 5) Add solution B to suspension C, stirring while adding dropwise, stirring rate 200 r / min; time: 1 h;

[0058] Then the aging, filtering, washing, drying, roasting and other processes are carried out in sequence. 0.9 Co 2.1 O 4- -PtCo / Al2O3 catalyst; aging process: room temperature: 15h. Washing: use deionized water, wash 3 times; drying process: 110℃@5h; continuous roasting process, the first roasting temperature: 400℃, time: 3h; the second roasting temperature: 750℃, time: 5h.

[0059] Example 6

[0060] This embodiment is similar to embodiment 1, except that the non-stoichiometric ratio of Ni 0.5 Co 2.5 O4 spinel content accounts for 10.0wt%, N 0.5 C 2.5 -4Pt1PdW / Al2O3 catalyst has a platinum-palladium content of 1.0 wt%, a platinum-palladium mass ratio of 4:1, and a transition metal WO3 content of 5.0 wt%. The preparation method is the same as that in Example 1 to prepare the catalyst of this example.

[0061] Comparative Example 1

[0062] The catalyst in this comparative example does not have transition metal W and non-stoichiometric Ni loaded on the catalytic material. 0.5 Co 2.5 O4 spinel, the active component of the catalyst is platinum and palladium, the mass ratio is 4:1, the content of precious metal platinum and palladium accounts for 1.0wt%, and the preparation method comprises the following steps:

[0063] 1) According to the content design, noble metal platinum nitrate and platinum nitrate salt are prepared into a mixed solution, and oxalic acid is added to form solution A, and the oxalic acid content and the noble metal content are added according to the molar ratio of 3:1;

[0064] 2) Place solution A in a water bath and stir continuously at a water bath temperature of 60°C for 2 hours. Add catalytic material alumina to solution A at a mass ratio of 0.9 to solution A; continue stirring at a water bath temperature of 60°C for 5 hours; then go through a muffle furnace drying and calcination process, drying process: 110°C @ 4 hours, calcination process: temperature: 400°C, time: 3 hours; obtain 4Pt1Pd / Al2O3 catalyst.

[0065] Comparative Example 2

[0066] This comparative example is similar to Example 1, except that in this comparative example, the catalytic material does not load transition metal W, and the active component is precious metal platinum and palladium, and the mass ratio is 4:1, the content of precious metal platinum and palladium accounts for 1.0wt%, and Ni x Co 3-x In O4 spinel nanoclusters, x is 0.5 and the non-stoichiometric ratio of Ni 0.5 Co 2.5 The content of O4 spinel is 5.0wt%, and the preparation method comprises the following steps:

[0067] 1) According to the content design, noble metal platinum nitrate and platinum nitrate are prepared into a mixed solution, and oxalic acid is added to form solution A, and the oxalic acid content and the noble metal content are added according to the molar ratio of 3:1;

[0068] Steps 2) to 5) are the same as those in Example 1 to prepare the catalyst of this comparative example.

[0069] Comparative Example 3

[0070] This comparative example is similar to Example 1, except that the catalyst material in this comparative example does not contain non-stoichiometric Ni 0.5 Co 2.5 O4 spinel, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, and the content of transition metal WO3 accounts for 5.0wt%. The preparation method is the same as steps 1) to 3) of Example 1 to prepare the catalyst of this comparative example.

[0071] Comparative Example 4

[0072] This comparative example is similar to Example 1, except that the catalyst material of this comparative example does not carry precious metals such as platinum and palladium. x Co 3-x In O4 spinel nanoclusters, x is 0.5, Ni 0.5 Co 2.5 The content of O4 spinel is 5.0wt%, and the content of transition metal WO3 is 5.0wt%. The catalyst is prepared by the following method:

[0073] 1) According to the designed content, ammonium metatungstate is prepared into a solution, and oxalic acid is added to form solution A;

[0074] Steps 2) to 5) are the same as those in Example 1 to prepare the catalyst of this comparative example.

[0075] Comparative Example 5

[0076] This comparative example is similar to Example 1, except that in the preparation method of this comparative example, step 5) is different, specifically: 5) adding solution B to the suspension, stirring while adding dropwise, with a stirring rate of 200 r / min; time: 1 h; then aging, filtering, washing, drying, roasting and other processes are carried out in sequence to obtain the catalyst of the comparative example; wherein the aging process is 15 h at room temperature; washing is performed 3 times with deionized water; the drying process is at 110°C@5 h; roasting adopts a single roasting process, the roasting temperature is: 750°C, and the time is 5 h.

[0077] Comparative Example 6

[0078] This comparative example is similar to Example 1, except that in this comparative example, the catalyst uses a stoichiometric ratio of NiCo2O4, the molar ratio of Ni to Co is 1:2, and in the catalyst, the stoichiometric ratio of NiCo2O4 spinel content accounts for 5wt%, the precious metal platinum palladium content accounts for 1.0wt%, the mass ratio of platinum to palladium is 4:1, and the transition metal WO3 content accounts for 5.0wt%. The catalyst is prepared by the following method:

[0079] Steps 1)-3) are the same as in Example 1;

[0080] 4) mixing corresponding precursor salts of nickel nitrate and cobalt nitrate at a molar ratio of Ni to Co of 1:2 and 5 wt% of the total mass of the catalyst to obtain solution B;

[0081] Step 5) is the same as in Example 1 to prepare the catalyst of this comparative example.

[0082] Comparative Example 7

[0083] This comparative example is similar to Example 1, except that the molar ratio of Ni to Co in the catalyst of this comparative example is 0.3:2.7, and the stoichiometric ratio of Ni in the catalyst is 0.3:2.7. 0.3 Co 2.7 The content of O4 spinel accounts for 5wt%, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, the content of transition metal WO3 accounts for 5.0wt%, and the catalyst is prepared by the following method:

[0084] Steps 1)-3) are the same as in Example 1;

[0085] 4) mixing corresponding precursor salts of nickel nitrate and cobalt nitrate at a molar ratio of Ni to Co of 0.3:2.7 and accounting for 5 wt% of the total mass of the catalyst to obtain solution B;

[0086] Step 5) is the same as in Example 1 to prepare the catalyst of this comparative example.

[0087] Comparative Example 8

[0088] This comparative example is similar to Example 1, except that in the preparation method of this comparative example, in step 5), solution B is not added dropwise, specifically:

[0089] Steps 1)-4) are the same as in Example 1;

[0090] 5) Solution B is directly added to the suspension and stirred for 1 hour; then aging, filtering, washing, drying, calcining and other processes are carried out in sequence to obtain the catalyst of this comparative example; wherein the aging process is 15 hours at room temperature; washing is performed 3 times with deionized water; the drying process is at 110°C@5h; a continuous calcination process is adopted, with the first calcination temperature: 400°C, time: 3h; the second calcination temperature: 750°C, time: 5h.

[0091] Comparative Example 9

[0092] This comparative example provides a catalyst, wherein Ni x Co 3-x In O4 spinel nanoclusters, x is 0.5, Ni 0.5 Co 2.5 The content of O4 spinel accounts for 5.0wt%, the content of precious metal platinum and palladium accounts for 1.0wt%, the mass ratio of platinum and palladium is 4:1, and the content of transition metal WO3 accounts for 5.0wt%. The preparation method is as follows:

[0093] 1) According to the content design, noble metal platinum nitrate, platinum nitrate and ammonium metatungstate are prepared into a mixed solution, and oxalic acid is added to form solution A, and the oxalic acid content and the noble metal content are added according to the molar ratio of 3:1;

[0094] 2) Place solution A in a water bath and stir continuously at 60°C for 2 hours. Add catalytic material aluminum oxide to solution A at a mass ratio of 0.9; continue stirring at 60°C for 5 hours;

[0095] 3) Prepare a sodium hydroxide-ammonia solution, add the sodium hydroxide-ammonia solution to solution A, adjust the pH control range to 10-10.5, stir continuously, and place in a water bath at 90° C. for 3 h to obtain a mixed solution A;

[0096] 4) With the molar ratio of Ni to Co being 0.5:2.5, according to Ni 0.5 Co 2.5 O4 is added to the catalyst at 5 wt% of the total mass, and the corresponding precursor salts of nickel nitrate and cobalt nitrate are mixed to obtain solution B;

[0097] 5) Add solution B to mixed solution A, stirring while adding dropwise, with a stirring rate of 200 r / min; time: 1 hour; then carry out aging, filtration, washing, drying, roasting and other processes in sequence to obtain the catalyst of this comparative example; wherein the aging process is 15 hours at room temperature; washing is performed 3 times with deionized water; the drying process is at 110°C@5h; a continuous roasting process is adopted, with the first roasting temperature: 400°C, time: 3h; the second roasting temperature: 750°C, time: 5h.

[0098] Test Example 1

[0099] The catalysts of the above-mentioned Examples 1-6 and Comparative Examples 1-9 are made into integral catalysts, specifically: the catalyst, water and adhesive are mixed and ball-milled in a mass ratio of 40:100:4, the adhesive is pseudo-boehmite, and the particle size after ball milling is controlled to be 3-10 μm, to prepare a catalyst slurry, and then the catalyst slurry is coated on a porous ceramic honeycomb carrier, requiring that the catalyst mass accounts for 25%, and after hot air drying at 60-90°C for 2-5h, and then calcined at 400-650°C for 3-5h, the integral catalyst can be obtained.

[0100] The prepared catalyst was used to test the low-temperature ignition performance and stability of propane. The concentration of the exhaust gas before and after passing through the catalyst was detected using a chromatograph. In the low-temperature ignition performance, the test object was propane (C3H8), the test atmosphere was O2: 2%, C3H8: 100ppm, H2O: 10vol%, and the balance gas was N2; the test air velocity was 25000h -1 , test temperature 250~450℃, temperature gradient: 5℃, test state is steady state. The test atmosphere in the stability test is O2: 2%, C3H8: 100ppm, H2O: 10vol%, balance gas: N2; the test air velocity is 25000h -1 , test temperature 350℃@200h. The test results are shown in Table 1 and Table 2 below, where the difference between the comparative example and the embodiment is calculated by comparing the comparative example with embodiment 1, and the fluctuation rate is the difference between the catalytic efficiency at the Xh and the catalytic efficiency at the 10h and the ratio of the catalytic efficiency at the corresponding time.

[0101] Table 1 Ignition temperature T of Examples 1-6 and Comparative Examples 1-9 50 and T 99 Test Results

[0102]

[0103] Table 2 Catalyst stability test results of Examples 1-6 and Comparative Examples 1-9

[0104]

[0105] Note: Since the performance of comparative example 4 was too poor, no stability test was performed.

[0106] According to the data in the above table, in the T of Examples 1-6 50 The temperature range is 290~315℃, T 99 The temperature range is 350-365°C. Except for Comparative Example 4, the T 50 The temperature range is 340-425℃, T 99 are all greater than 380°C, which shows that the T 50 and T 99 The ignition performance is significantly better than that of the comparative example. By comparing Examples 1-6 with Comparative Examples 1-3, it is shown that Ni x Co 3-x O4 spinel nanoclusters and transition metals and noble metals work together to significantly reduce T 50 and T 99 This indicates that the ignition performance of the prepared product is excellent, which is mainly due to the non-stoichiometric Ni x Co 3-x O4 spinel nanoclusters exhibit good redox properties and have more defect sites. At the same time, transition metals promote the noble metal active sites to be more metal valence active sites, thereby further synergistically improving the adsorption and cracking of propane and achieving better low-temperature ignition. x Co 3-x O4 spinel nanoclusters or transition metals cannot achieve significant benefits. Combined with Comparative Example 4, it further illustrates that relying on Ni X Co 3-x O4 spinel nanoclusters, transition metals and precious metals, to achieve the beneficial effects of this patent. By comparing Example 1 with Comparative Example 5, it is shown that the performance of using two roastings is better than that of one roasting. This is mainly to ensure that Ni X Co 3- x O4 spinel nanoclusters have better particle size distribution and stability, and enhance the interaction with catalytic materials, which is more conducive to the low-temperature ignition performance of the transition metal and precious metal and the stability of the catalyst. Among them, the catalyst of comparative example 4 has poor catalytic performance because it has no precious metal active sites. At 450°C, the conversion efficiency of propane is only 6.2%, which cannot be compared with the performance of catalysts containing precious metal activity. This is mainly because the precious metal active sites are the main contributors to the catalytic oxidation of propane.

[0107] The present invention can be achieved by regulating Ni X Co 3-x The ratio of Ni and Co in O4 spinel nanoclusters, Ni X Co 3-xThe content of O4 spinel nanoclusters and the type of transition metal are used to prepare a catalyst for catalytic oxidation of light alkanes, and at the same time, the preparation method of the present invention is combined to achieve good low-temperature ignition performance and significantly reduce T 50 and T 99 Comparative Examples 6 to 9 illustrate the use of non-stoichiometric Ni X Co 3-x The content of O4 spinel nanoclusters and the importance of particle size control, especially in Comparative Examples 8 and 9, further illustrate the importance of Ni X Co 3-x The excessive size of O4 spinel nanoclusters and the failure to adopt step-by-step calcination will lead to serious inadequacy of catalyst performance and fail to achieve the significant benefits of this patented invention.

[0108] The stability test was conducted at 350°C. The catalytic efficiency of the catalysts prepared by the method of the present invention in Examples 1-6 can reach more than 93%, and can maintain good stability for a test time of 200 hours. The fluctuation range of the catalytic efficiency is less than 1.0%, and it still has good stability at a high conversion rate. For the stability test of the comparative examples, the catalytic efficiency of Comparative Examples 1-9 is relatively low at 350°C. Except for Comparative Example 4, Comparative Examples 1 to 7 have relatively good stability, and the fluctuation range of the catalytic efficiency is less than 6.3% within 200 hours; Comparative Examples 8 to 9 have poor stability, and the fluctuation range of the catalytic efficiency is greater than 10% within 50 hours to 200 hours. This is mainly due to the non-stoichiometric Ni X Co 3-x The O4 particles are large in size, unevenly distributed, and cannot form good synergy with the precious metal active components.

[0109] For those skilled in the art, when understanding the solutions described in the specific embodiments of the present invention, they can refer to the conventional technical manuals in the field. At the same time, for the places where the above-mentioned terms appear, they can make appropriate understandings or adjustments for reference, and deduce the implementation of the same or similar technical solutions without paying any creative work.

[0110] The above embodiments describe only the basic principles, main features and / or advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and the invention content of the specification only describe the principles or specific cases of the present invention. Without departing from the essence of the innovative idea of ​​the present invention, the innovative scheme of the present invention may be subject to various changes and improvements, and these changes and improvements all fall within the scope of protection required by the present invention.

Claims

1. A low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes, characterized in that: The catalyst comprises a catalytic material and an active component supported on the catalytic material, Ni x Co 3-x O4 spinel nanoclusters, x is 0.4 to 0.99, the active component is a composite metal oxide composed of a noble metal and a transition metal, the catalyst is prepared by first combining the active component with the catalytic material, and then combining with the Ni x Co 3-x O4 spinel nanoclusters are combined; in the catalyst, the Ni x Co 3-x The content of O4 spinel nanoclusters accounts for 1.0-20.0wt%; the content of the noble metal accounts for 0.1-2.0wt%; and the content of the transition metal accounts for 1.0-20.0wt%.

2. A low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to claim 1, characterized in that: The noble metal is at least one of Pt and Pd, and the content of the noble metal accounts for 0.5-1 wt %.

3. A low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to claim 1, characterized in that: The Ni x Co 3-x The content of O4 spinel nanoclusters is 5-15.0wt%.

4. A low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to claim 1, characterized in that: The transition metal is at least one of tungsten, cobalt, molybdenum, niobium, nickel, zirconium, titanium, vanadium and manganese, and the content of the transition metal accounts for 3.0 to 15.0 wt%.

5. The low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to claim 1, characterized in that: The catalytic material is at least one of aluminum oxide, silicon oxide, titanium oxide, cerium oxide and zirconium oxide.

6. The method for preparing a low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Prepare a mixed solution of soluble precursor salts of precious metals and transition metals, add a first auxiliary agent to form solution A, stir solution A at a temperature of 40 to 90° C. for 1 to 4 hours, then add a catalytic material to solution A, the mass ratio of the catalytic material added to solution A is 0.8 to 1.2, and continue stirring at a temperature of 40 to 90° C. for 3 to 10 hours. After completion, dry and calcine to obtain a PT / M catalyst; A sodium hydroxide-ammonia aqueous solution with a pH of 8.5 to 11 is prepared to obtain a solution C, the PT / M catalyst is added to the solution C, and a suspension containing the PT / M catalyst is obtained after stirring, and the suspension is kept at a temperature of 40 to 90° C. for 1 to 6 hours; A mixed solution of a nickel soluble precursor salt and a cobalt soluble precursor salt is prepared to obtain a solution B, wherein the molar ratio of Ni to Co is x:(3-x), and x is 0.4 to 0.99; S2. Add the solution B dropwise into the suspension under stirring, with a stirring rate of 100 to 300 r / min and a dropping duration of 1 h to 3 h; then age, filter, wash, dry and calcine in sequence to obtain a catalyst for catalytic oxidation of light alkanes.

7. The method for preparing a low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to claim 6, characterized in that: The first auxiliary agent is at least one of citric acid and oxalic acid, and the first auxiliary agent content and the noble metal content are added in a molar ratio of 1.5 to 5:

1.

8. The method for preparing a low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to claim 6, characterized in that: The conditions of the aging process are aging at room temperature for 10 to 24 hours; The washing process uses deionized water for 1 to 3 times; The drying process conditions are drying at 90-120°C for 5-10 hours.

9. The method for preparing a low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes according to any one of claims 6 to 8, characterized in that: The roasting adopts a continuous roasting process and is divided into two roasting times. The first roasting condition is roasting at 300-450°C for 3-5 hours; the second roasting condition is roasting at 650-900°C for 3-7 hours.

10. A monolithic catalyst comprising a carrier and a catalytic coating, characterized in that: The catalytic coating comprises a low-temperature and high-efficiency catalytic oxidation catalyst for light alkanes as described in any one of claims 1-5.

Citation Information

Patent Citations

  • Surface strengthening-type palladium-based catalyst for catalytic combustion of low concentration methane and preparation method thereof

    CN105457653A

  • Preparation method of novel noble metal Pd-loaded NiCo2O4 spinel catalyst

    CN111054391A

  • Hydrodealkylation of alkylaromatic hydrocarbons

    US4247730A

  • Metal-containing spinel composition and process of using same

    US4790982A